2005
DOI: 10.1177/112067210501500612
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Perimetry, Short-Wavelength Automated Perimetry, Frequency-Doubling Technology, and Visual Evoked Potentials in the Assessment of Patients with Multiple Sclerosis

Abstract: Short-wavelength automated perimetry and FDT perimetry are two non-conventional perimetric techniques that were mainly developed for the early detection of glaucomatous damage. The results of this study demonstrate their efficacy also in detecting early visual field deficits in MS patients without clinical signs of optic neuropathy. Frequency doubling perimetry, in particular, proved to be an easy, fast, and sensitive technique in the assessment of patients with MS. Our results also suggest that subclinical vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Contrary to our study, Corallo et al used a test of central limit 30-2 (76 targets tested). This analysis of the visual field larger than the one given by FDTP, which is limited to 20°, could explain this absence of correlation, as well as the smaller sample size of only fourteen patients [23].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Contrary to our study, Corallo et al used a test of central limit 30-2 (76 targets tested). This analysis of the visual field larger than the one given by FDTP, which is limited to 20°, could explain this absence of correlation, as well as the smaller sample size of only fourteen patients [23].…”
Section: Resultsmentioning
confidence: 95%
“…Apart from underlining the campimetric deficits among patients with a previous history of ON, FDTP allowed, among patients without a previous history of ON, the detection of anomalies of the visual field due to an axonal deficit consecutive to infra-clinical demyelinating lesions of the optic nerve [21,22]. FDTP would be more sensitive than SAP in detecting the first campimetric alterations [23]. The large retinal ganglionic cells (M cells) are less numerous and less redundant; their effect would explain more precocious alterations to the visual field.…”
Section: Resultsmentioning
confidence: 98%
“…Visual evoked potentials anomalies in 43.7% of MS patients with negative ophthalmological examination were described by Corallo et al (2005), who concluded that a combination of several diagnostic techniques could identify asymptomatic optic nerve impairment. In a similar study group, but one that included subjects with a normal VF examination, we observed 40% of eyes to have a prolonged P100 latency.…”
Section: Discussionmentioning
confidence: 99%
“…18 Correlations between RNFL morphology and neurophysiology are also reported. 19,20 Consideration of patient quality of life (QOL) is intrinsic to the practice of medicine, particularly when evaluating therapeutic approaches to chronic disease. 21 In PD, fatigue and fatigability levels are higher than in healthy individuals, and are negatively associated with QOL scores.…”
mentioning
confidence: 99%